L’accomplissement interactionnel de l’autonomie - Marianne Zogmal (Revue d'anthropologie des connaissances)
In care professions, the notion of autonomy of the care beneficiaries is often central in texts and professional discourse. In an interactional perspective of workplace analysis, this contribution focuses on the professional practices in Early Childhood Education, actually mobilized to promote the autonomy of young children. Pre-existing knowledge on the concept of autonomy is discussed historically and across different disciplinary perspectives. Then, the empirical analysis relates to a activity conducted with a group of children during a professional internship in the third year of ES Educator training as well as the subsequent evaluation. Audio-video recordings allow a detailled analysis of the interactional process. This article highlights the gap between the effective professional practices and the stated purpose of the activity of letting children play by themselves. This difference and its occultation limit the dialogue between everyday knowledge and disciplinary perspectives. For educators themselves, this restricts the possibilities for: a) explain their practices and debate; b) acquire and transmit professional competences; c) contribute to social recognition of the professional practices in Early Childhood Education. For research perspectives, this article shows that a detailed interactional analysis of actual practices allows to overcome some occultation phenomena and enlighten the concept of autonomy in its complexity.